Effects of valsartan, benazepril and their combination in overt nephropathy of type 2 diabetes: A prospective, randomized, controlled trial. Issue 5 (22nd February 2019) - Ruggenenti, Piero; Trillini, Matias; P. Barlovic, Drazenka; Cortinovis, Monica; Pisani, Antonio; Parvanova, Aneliya; Iliev, Ilian P.; Ruggiero, Barbara; Rota, Stefano; Aparicio, Maria C.; Perna, Annalisa; Peraro, Francesco; et al.
Abstract : Aims: To evaluate whether angiotensin‐converting enzyme (ACE) inhibitor and angiotensin II receptor blocker (ARB) combination therapy is more nephroprotective than ACE inhibitor or ARB monotherapy in people with type 2 diabetes and overt nephropathy. Materials and methods: In this prospective, randomized, open, blind‐endpoint phase III trial sponsored by the Italian Drug Agency, 103 consenting patients with type 2 diabetes, aged >40 years, with serum creatinine levels 159 to 309 μmol/L, spot morning urinary albumin–creatinine ratio > 1000 mg/g (or > 500 mg/g in those on ACE inhibitor or ARB therapy at inclusion) were stratified by centre and randomized to 4.5‐year treatment with valsartan 320 mg/d (n = 36), benazepril 20 mg/d (n = 34) or halved doses of both medications (n = 33). The primary endpoint was end‐stage renal disease (ESRD). Modified intention‐to‐treat analyses were performed. Results: Recruitment took place between June 2007 and February 2013 at 10 centres in Italy and one in Slovenia. A total of 77 participants completed the study and 26 were prematurely withdrawn. During a median (interquartile range) of 41 (18–54) months, 12 participants on benazepril (35.3%) and nine on combination therapy (27.3%) progressed to ESRD, versus five on valsartan (13.9%). Differences between benazepril (hazard ratio [HR] 3.59, 95% confidence interval [CI] 1.25–10.30; P = 0.018) or combination therapy (HR 3.28, 95% CI 1.07–10.0; P = 0.038) and valsartan were significant, even after adjustment for age, gender and baseline serum creatinine, systolic blood pressure and 24‐hour proteinuria (HR 5.16, 95% CI 1.50–17.75, P = 0.009 and HR 4.75, 95% CI 1.01–22.39, P = 0.049, respectively). Adverse events were distributed similarly among the groups. Conclusions: In people with type 2 diabetes with nephropathy, valsartan (320 mg/d) safely postponed ESRD more effectively than benazepril (20 mg/d) or than halved doses of both medications.